Analysis of Sharia Brand Image and Facilities on Customer Decision Making to Choose BMT Beringharjo Ponorogo Branch with Trust as a Mediating Variable - Muhammad Ridlo Zarkasyi; Robi Sugih Alamsyah; Dhika Amalia Kurniawan (Al Tijarah, 2024)
The financial sector is an institution that provides financial services to commercial and retail customers, including investment funds, banks, insurance and co-operatives. One finance sector is the BMTs in East Java province is BMT Beringharjo Ponorogo Branch. BMT Beringharjo Ponorogo in addition to serving fund deposits also serves mudharabah financing in order to empower the community to improve their business and get out of the poverty circle. The approach used this thesis is a quantitative approach. That way quantitative research departs from a theory towards data to test the truth of the theory. The result from this study is Sharia Brand Image variable has a positive influence on the decision making of members choosing BMT Beringharjo financial institutions. Facility variables have a positive influence on the decision making of members choosing BMT Beringharjo financial institutions. Trust variables can mediate between Sharia Brand Image on members'' decisions to choose financial institutions because Sharia Brand Image has a significant positive effect, this is because the better the Sharia Brand Image that BMT Beringharjo has, the higher the member''s trust in the financial institution.